Improving cardiac reprogramming for heart regeneration. Issue 6 (December 2016) - Liu, Liu; Lei, Ienglam; Wang, Zhong
Abstract : Purpose of review: Cardiovascular disease is the leading cause of death in the world today, and the death rate has remained virtually unchanged in the last 20 years (American Heart Association). This severe life-threatening disease underscores a critical need for developing novel therapeutic strategies to effectively treat this devastating disease. Cell-based therapy represents an extremely promising approach. Generation of induced cardiomyocytes (iCMs) directly from fibroblasts offers an attractive novel strategy for in-situ heart regeneration. Major challenges of iCM reprogramming include the low conversion rate and heterogeneity of the iCMs. This review will summarize the major advancements in improving the iCM reprogramming efficiency and iCM maturation. Recent findings: Numerous studies have been published in the past 18 months to describe various strategies for achieving more efficient iCM reprogramming. These strategies are based on our understanding of the molecular mechanisms of cardiogenesis, which include transcriptional networks, signaling pathways and epigenetic cell fate change. Summary: Novel strategies for highly efficient iCM reprogramming will be required for applying iCM reprogramming to patients. Creative and combined methods based on our understanding of cardiogenesis will continue to contribute heavily in the advancement of iCM reprogramming. We are highly optimistic that iCM reprogramming-based heart therapy will restore the pumping function of damaged patient hearts.